EFEKTIVITAS DIGITALISASI PADA TRANSFORMASI LABORATORIUM KLINIK MELALUI SISTEM INFORMASI LABORATORIUM - Agnes Liana Sutrisno; Dasrum Hidayat; Rizki Adriansyah Rubini (Journal of Innovation Research and Knowledge, 2024)
This study aims to analyze the effectiveness of digitalization in the transformation of services at Pramita Clinical Laboratory through the implementation of the Laboratory Information System (LIS). Digitalization is considered an important step to improve operational efficiency, data accuracy, and process speed in laboratory services. This study uses a quantitative method by collecting data through surveys and interviews with laboratory staff and patients, as well as data analysis from the LIS system that has been implemented. The results of the study indicate that digitalization through LIS can increase the efficiency of data processing time, reduce human error, and improve the quality of services provided to patients. In addition, the implementation of LIS also has a positive impact on patient satisfaction and the performance of medical personnel, which overall supports the improvement of service quality at Pramita Clinical Laboratory. However, this study also found several obstacles, such as user adaptation and the need for adequate training. In conclusion, digitalization through the Laboratory Information System is effective in supporting the transformation of laboratory services, although ongoing management is needed to optimize its implementation